Insights into formation scenarios of massive early-type galaxies from spatially resolved stellar population analysis in CALIFA. Issue 3 (25th November 2019) - Zibetti, Stefano; Gallazzi, Anna R; Hirschmann, Michaela; Consolandi, Guido; Falcón-Barroso, Jesús; van de Ven, Glenn; Lyubenova, Mariya
ABSTRACT: We perform spatially resolved stellar population analysis for a sample of 69 early-type galaxies (ETGs) from the CALIFA integral field spectroscopic survey, including 48 ellipticals and 21 S0's. We generate and quantitatively characterize profiles of light-weighted mean stellar age and metallicity within ≲2 R e, as a function of radius and stellar-mass surface density μ* . We study in detail the dependence of profiles on galaxies' global properties, including velocity dispersion σe, stellar mass, morphology. ETGs are universally characterized by strong, negative metallicity gradients ($\sim \!-0.3\, \text{dex}$ per R e ) within 1 R e, which flatten out moving towards larger radii. A quasi-universal local μ* –metallicity relation emerges, which displays a residual systematic dependence on σe, whereby higher σe implies higher metallicity at fixed μ* . Age profiles are typically U-shaped, with minimum around 0.4  R e, asymptotic increase to maximum ages beyond $\sim 1.5\, $ R e, and an increase towards the centre. The depth of the minimum and the central increase anticorrelate with σe . A possible qualitative interpretation of these observations is a two-phase scenario. In the first phase, dissipative collapse occurs in the inner 1 R e, establishing a negative metallicity gradient. The competition between the outside-in quenching due to feedback-driven winds and some form of inside-out quenching, possibly caused by central AGN feedback or dynamical heating, determines the U-shaped age profiles. In the second phase, the accretion of ex-situ stars from quenched and low-metallicity satellites shapes the flatter stellar population profiles in the outer regions.